The topical application of low-temperature argon plasma enhances the anti-inflammatory effect of Jaun-ointment on DNCB-induced NC/Nga mice - Jeong-Hae Choi; Yeon-Suk Song; Hae-June Lee; Gyoo-Cheon Kim; Jin-Woo Hong (BMC, 2017)
Abstract Background Jaun-ointment (JO), also known as Shiunko in Japan, is one of the most popular medicinal formulae used in Korean traditional medicine for the external treatment of skin wound and inflammatory skin conditions. Since JO is composed of crude mixture of two herbal extracts (radix of Lithospermum erythrorhizon Siebold & Zucc and Angelica gigas Nakai), those been proved its anti-inflammatory activities in-vitro and in-vivo, JO has been expected as a good alternative treatment option for atopic dermatitis (AD). However, due to the lack of strategies for the penetrating methods of JO's various anti-inflammatory elements into the skin, an effective and safe transdermal drug delivery system needs to be determined. Here, low-temperature argon plasma (LTAP) was adopted as an ancillary partner of topically applied JO in a mice model of AD and the effectiveness was examined. Methods Dorsal skins of NC/Nga mice were challenged with DNCB (2,4-dinitrochlorobenzene) to induce AD. AD-like skin lesions were treated with JO alone, or in combination with LTAP. Inflammatory activity in the skin tissues was evaluated by histological analysis and several molecular biological tests. Results LTAP enhanced the effect of JO on AD-like skin lesion. Topical application of JO partially inhibited the development of DNCB-induced AD, shown by the moderate reduction of eosinophil homing and pro-inflammatory cytokine level. Combined treatment of JO and LTAP dramatically inhibited AD phenotypes. Interestingly, treatment with JO alone did not affect the activity of nuclear factor (NF)κB/RelA in the skin, but combined treatment of LTAP-JO blocked DCNB-mediated NFκB/RelA activation. Conclusions LTAP markedly enhanced the anti-inflammatory activity of JO on AD-like skin lesions. The effect of LTAP may be attributed to enhancement of drug penetration and regulation of NFκB activity. Therefore, the combination treatment of JO and LTAP could be a potential strategy for the treatment of AD.